2015
DOI: 10.1016/j.pupt.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as an adjunctive therapy in asthma. Part 2: A review of human studies

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Emerging evidence suggests that VDD is associated with increased airway hyperresponsiveness, decreased pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 176 publications
2
39
2
8
Order By: Relevance
“…In an animal study on diabetic rats, it was demonstrated that treatment with VD for 12 weeks increased the serum level of T in treatment groups. [26] In a clini- Abnormalities in calcium and phosphorus homeostasis [10,15] Bronchial asthma [4,7] Coronary artery disease [14,16] Erectile dysfunction [9,17,18] Heart failure [10,16] Hypertension [9,14] Hypogonadism [19][20][21][22] Impaired vascular endothelial and smooth muscle function [9,16] Increased immune or inflammatory response [23,24] Infertility [25,26] Metabolic syndrome [10,14,27] Osteoporosis [19,28,29] Peripheral vascular disease [15,30] Respiratory diseases [3,4] Wearing sunscreen clothes cal randomized controlled trial, which is the first on this topic in literature, Pilz et al [39] investigated the effect of VD supplementation on androgens in men. The results were significant and the researchers observed that overweight men with VDD had a clinically meaningful increase in serum T levels after VD supplementation for 1 year.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In an animal study on diabetic rats, it was demonstrated that treatment with VD for 12 weeks increased the serum level of T in treatment groups. [26] In a clini- Abnormalities in calcium and phosphorus homeostasis [10,15] Bronchial asthma [4,7] Coronary artery disease [14,16] Erectile dysfunction [9,17,18] Heart failure [10,16] Hypertension [9,14] Hypogonadism [19][20][21][22] Impaired vascular endothelial and smooth muscle function [9,16] Increased immune or inflammatory response [23,24] Infertility [25,26] Metabolic syndrome [10,14,27] Osteoporosis [19,28,29] Peripheral vascular disease [15,30] Respiratory diseases [3,4] Wearing sunscreen clothes cal randomized controlled trial, which is the first on this topic in literature, Pilz et al [39] investigated the effect of VD supplementation on androgens in men. The results were significant and the researchers observed that overweight men with VDD had a clinically meaningful increase in serum T levels after VD supplementation for 1 year.…”
Section: Vitamin D and Endocrine Systemmentioning
confidence: 99%
“…[3][4][5][6] VD receptor is a member of the steroid receptor superfamily. Strikingly, over 3,000 genes are responsive to VD [7] and its biological effects are mediated through binding to the VD receptor and inducing either genomic or non-genomic downstream effects (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans may obtain vitamin D via two major sources: endogenous synthesis in the skin after UVB light exposure and diet (intake of vitamin D rich products such as fish, fish oils, egg yolk, liver and dietary supplements) [3,4]. In the skin, 7-dehydrocholesterol is converted to previtamin D due to action of UVB rays and then transformed to cholecalciferol via thermally induced isomerization.…”
Section: Vitamin D Synthesis Metabolism and Mechanism Of Actionmentioning
confidence: 99%
“…
We have recently reviewed that many mechanisms (1) and human studies (2) linking vitamin D deficiency (VDD) to asthma. Associations between vitamin D and both asthma/allergy appear stronger in children than adults (3) , with some even suggesting that childhood asthma may be caused by VDD (4) .
…”
mentioning
confidence: 99%